2020
DOI: 10.1002/pc.25624
|View full text |Cite
|
Sign up to set email alerts
|

Tailored piezoelectric performance of self‐polarized PVDF‐ZnO composites by optimization of aspect ratio of ZnO nanorods

Abstract: Aspect ratio of filler plays a crucial role to study the electrical properties of polymer based composite system. Here, we investigated the effect of filler aspect ratio on the electrical properties of zinc oxide (ZnO) incorporated poly(vinylidene fluoride) (PVDF) matrix. ZnO nanorods having different aspect ratio were synthesized by the hydrothermal technique with varying reaction time 4 to 20 hours at a fixed temperature and PVDF based nanocomposites of the respective ZnO nanorods with different wt% filler l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…[30] Polymer nanocomposites based on ZnO nanoparticles are extensively studied due to their unique structural, rheological, thermal, electrical, energy harvesting, mechanical, and antimicrobial properties. [31][32][33] Shanshool et al studied the optical properties of ZnO nanoparticles reinforced polymers such as poly(methyl methacrylate), poly(vinylidene fluoride), polyvinyl alcohol and polystyrene. [34] Sen et al reported the methane detection capability of PANI/ZnO nanocomposites at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Polymer nanocomposites based on ZnO nanoparticles are extensively studied due to their unique structural, rheological, thermal, electrical, energy harvesting, mechanical, and antimicrobial properties. [31][32][33] Shanshool et al studied the optical properties of ZnO nanoparticles reinforced polymers such as poly(methyl methacrylate), poly(vinylidene fluoride), polyvinyl alcohol and polystyrene. [34] Sen et al reported the methane detection capability of PANI/ZnO nanocomposites at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[21] This method is prone to increase leakage current, which leads to increased dielectric loss, and it is difficult to obtain a high breakdown electric field. [22][23][24] The second method is to add high dielectric constant ceramic nanoparticles in the polymer matrix, [25] such as barium titanate (BaTiO 3 , BT), [26,27] ZnO, [28] BCZT. [29] This method combines the high breakdown electric field of the polymer matrix with the advantages of high dielectric constant and low dielectric loss of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the facts mentioned above, researchers then tried to change the different physiochemical properties of the fillers. For this purpose, fillers with external charging, [37] changing the surface charge of fillers by chemical route, [17] changing the size [184][185][186] and shape [187,188] of fillers, addition of third conducting phase, [189][190][191] fabrication of ternary Figure 9. Schematic presentation of some interfacial interaction mechanism of PVDF dipoles with filler surface (BiFeO 3 and hydroxylated BiFeO 3 for this particular case).…”
Section: Tailoring the Physiochemical Properties Of The Additive Phasementioning
confidence: 99%